Interregional comparison of benthic ecosystem functioning: Community bioturbation potential in four regions along the NE Atlantic shelf. (March 2020) - Gogina, Mayya; Zettler, Michael L.; Vanaverbeke, Jan; Dannheim, Jennifer; Van Hoey, Gert; Desroy, Nicolas; Wrede, Alexa; Reiss, Henning; Degraer, Steven; Van Lancker, Vera; Foveau, Aurélie; Braeckman, Ulrike; et al.
Highlights: First multi-regional analysis of macrofauna community bioturbation potential (BPc ). Functionally important key species differ regionally and between sediments. Overall BPc values decreased from the Baltic Sea towards Eastern English Channel. Relevance of BPc for ecosystem functions vary with biotic and abiotic settings. Results accent the need for region-specific conservation and management strategies. Abstract: Bioturbation is one of the key mediators of biogeochemical processes in benthic habitats that can have a high contribution to seafloor functioning and benthic pelagic coupling in coastal waters. Previous studies on bioturbation were limited to point locations and extrapolations in single regions, but have not accounted for regional differences under changing environmental conditions, though there are indications that species contributions will differ across regions or with biotic and abiotic context. To capture those differences and assess global patterns and commonalities, multi-regional analyses are imperative. Here for the first time, bioturbation potential (BPc ), a functional indicator of benthic community bioturbation, was estimated based on macrofauna data from four regions (i.e. German Baltic Sea, German North Sea, Belgian part of the North Sea and the Eastern English Channel). For each region and sediment type we identified key species contributing to BPc . Comparison within and across regions demonstrated regional differences, and both overlap and mismatch between species that are functionally important and those that are dominant in biomass. Knowledge on the functionally important species is crucial when management objectives include the protection of certain ecosystem functions. Available environmental layers were used as predictors to model the spatial distribution of BPc for each area and to explore the underlying drivers of differences. Random forest models were trained using as response variables either i) BPc initially calculated per station; or ii) BPp – the species-specific contribution to BPc – for key species (with subsequent summation of their predicted full-coverage distributions to BPc ). Maps of BPc distribution predicted by random forest were compared with those generated using natural neighbour interpolation. Overall, derived BPc values increased towards the German parts of the North and Baltic Seas. The relevance of BPc for ecosystem processes and functions, however, vary with biotic and abiotic settings. Results revealed a strong association of BPc with species diversity and region, but less with sediment grain size. A large range of BPc occurred when species richness was low. This suggests that the provisioning of high bioturbation activity is possible also under low diversity, where it is vulnerable due to reduced resilience. The executed multi-regional analysis allowed identifying regional differences in performance of macrofauna, suggesting the need for region-specific conservation and management strategies.